Now or never: Organizational forgetting as a determinant of knowledge sharing and cross-boundary innovation - Qu, Xiaoyu; Khan, Adnan; Ali, Sajjad (Frontiers in Psychology, 2022)
This study constructs a theoretical model to test and prove that organizational forgetting influences cross-boundary innovation and testifies the moderating role of Institutionalized organizational mission in the said relationship. Data was collected through a convenient sampling technique from 353 middle and senior managers of entrepreneurial enterprises in China through online and offline modes. Additionally, we used confirmatory factor analysis, multiple regression analysis, and bootstrap analysis to verify hypotheses using AMOS and SPSS’s latest versions. The results show that organizational forgetting has a significantly positive impact on cross-boundary innovation and binary knowledge sharing plays a mediating role in the relationship between organizational forgetting and cross-boundary innovation. Moreover, the mediating effect of exploitative knowledge sharing on the relationship between organizational forgetting and cross-boundary innovation is more substantial than exploratory knowledge sharing. This study separates the impact mechanism of exploitative and exploratory knowledge sharing as a mediator unanimously and proves that Institutionalized organizational mission has a significant moderating role in the relationship between organizational forgetting and cross-boundary innovation. This research offers significant implications for Chinese enterprises to bolster cross-boundary innovation to achieve growth．